Konstruksi Citra Keluarga melalui Public Relation Organisasi - Ahmad Nadhim Ayatullah; Oji Kurniadi (Bandung Conference Series: Public Relations, 2022)
Abstract. Drama is an audio-visual work that uses television as its transmission medium. The average duration per episode is 60 – 90 minutes and airs once a week. The story in the drama is usually interesting and ends with a certain memory statement so that the audience can continue the next episode to understand the ending of the drama. South Korea is one of the developed countries that doubles its creative industry, such as K-pop music dramas and films, the Korean government also contributes to the creative arts industry. And in 2020 until now there has been an increase in Korean drama audiences in the world, judging by the effects of the pandemic, which makes people have to do everything at home. This study aims to describe the construction of the family image represented in the Korean drama "Graceful Family" The focus of this research is how TOP's public relations construct the family image of MC Group in the drama "Graceful Family" which has 16 episodes and a duration of 65-78 minutes / 108 minutes in the last episode. This study uses qualitative research, where data analysis uses the semiotic model of Charles Sander Peirce, Pierce categorizes the triangle theory of meaning, namely signs, objects, and interpretants. The researcher conducted an analysis of the selection of texts and images related to the construction of the MC Group family image. The results of this study indicate that the drama "Graceful Family" contains a lot of image construction in the form of strategies, roles, and meanings built by a Public Relations. Image construction is an image formation process that is formed to describe the perception of an individual, organization, company as a public image of it. Abstrak. Drama merupakan karya audio visual yang menggunakan televisi sebagai media transmisinya. Rata rata durasi per episodenya 60 – 90 menit dan tayang 1 minggu 1kali. Cerita di drama biasanya menarik dan di akhiri dengan pernyataan memori tertentu sehingga penonton dapat melanjutkan episode selanjutnyta untuk memahami alhir dari drama itu. Korea selatan adalah salah satu negara maju yang mengandakan industri kreatifnya, seperti drama musik Kpop dan film, pemerintah korea juga turut kontibutif dalam industri kreatif seni. Dan pada tahun 2020 sampai sekarang adanya peningkatan penonton drama koraa di dunia, di lihat dari efek pandemi juga yang membuat org harus melakukan segala sesuatu di rumah. Penelitian ini bertujuan untuk mendeskripsikan konstruksi citra keluarga yang direpesentasikan dalam drama Korea “Graceful Family” fokus penelitian ini adalah bagaimana cara public relation TOP mengonstruksi citra keluarga MC Group dalam drama “Graceful Family” yang memiliki 16 episode dan durasi 65-78menit / 108menit diepisode terakhir. Penelitian ini menggunakan penelitian kualitatif, yang dimana analisis data mengunakan semiotika model Charles Sander Peirce, Pierce mengkategorikan teori segitiga makna yaitu tanda, objek, dan interpretan. Peneliti melakukan analisis terhadap pemilihan teks dan gambar yang berhubungan dengan konstruksi citra keluarga MC Group. Hasil penelitian ini menunjukan bahwa drama “Graceful Family” banyak mengandung konstruksi citra berupa strategi, peran, dan makna yang dibangun oleh seorang Public Relation. Konstruksi citra adalah suatu proses pembentukan citra yang dibentuk muntuk menggambarkan persepsi dari suatu individu, organisasi, perusahaan sebagai gambaran publik terhdadapnya